2010
DOI: 10.1007/s10886-010-9745-y
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinones and Anthraquinones from Scent Glands of a Dyspnoid Harvestman, Paranemastoma quadripunctatum

Abstract: Extracts of Paranemastoma quadripunctatum (Opiliones, Dyspnoi, Nemastomatidae) contained seven components, all of which likely originated from the secretion of well-developed prosomal scent glands. The two main components (together accounting for more than 90% of the secretion) were identified as 1,4-naphthoquinone and 6-methyl-1,4-naphthoquinone. The minor components were 1,4-naphthalenediol, two methoxy-naphthoquinones (2-methoxy-1,4-naphthoquinone, and 2-methoxy-6-methyl-1,4-naphthoquinone) and two anthraqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 12 publications
(20 reference statements)
0
42
0
Order By: Relevance
“…Therefore, we propose that hydroquinones and their respective benzoquinones should be considered synonymous, if used for phylogenetic purposes. The identification of defensive compounds from the suborders Cyphophthalmi (Jones et al 2009;Raspotnig et al 2005Raspotnig et al , 2012 and Dyspnoi (Raspotnig et al 2010(Raspotnig et al , 2014bSchaider et al 2011) has allowed more precise inferences about the evolution of the defensive secretions in Opiliones (e.g., Raspotnig et al 2014a). As pointed out by these authors, knowing the biosynthetic routes of the defensive secretion is important because it allows a more realistic use of chemical data for phylogenetic purposes (e.g., proposing weight matrices).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we propose that hydroquinones and their respective benzoquinones should be considered synonymous, if used for phylogenetic purposes. The identification of defensive compounds from the suborders Cyphophthalmi (Jones et al 2009;Raspotnig et al 2005Raspotnig et al , 2012 and Dyspnoi (Raspotnig et al 2010(Raspotnig et al , 2014bSchaider et al 2011) has allowed more precise inferences about the evolution of the defensive secretions in Opiliones (e.g., Raspotnig et al 2014a). As pointed out by these authors, knowing the biosynthetic routes of the defensive secretion is important because it allows a more realistic use of chemical data for phylogenetic purposes (e.g., proposing weight matrices).…”
Section: Discussionmentioning
confidence: 99%
“…Harvestmen defensive secretions may be composed of methyl ketones, naphtoquinones, benzoquinones, and phenols among other chemicals (e.g., Hara et al 2005;Jones et al 2009;Raspotnig et al 2005Raspotnig et al , 2010Raspotnig et al , 2014aWouters et al 2013). Although these chemicals can repel some predators (Eisner et al 2004;Machado et al 2005), defensive secretions are not always used against all predators (see Carvalho et al 2012;Dias and Willemart 2013;Dias et al 2014;Eisner et al 2004;Souza and Willemart 2011;Segovia et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography (GC) (Raspotnig et al 2010;Zuo et al 2008), Raman microscopy (Beattie et al 2007), high-performance liquid chromatography (HPLC) (Sakunphueak and Panichayupakaranant 2010;Xue et al 2008), and mass spectrometry (MS) (Zhao et al 2010) Scheme 2 Illustration, using benzoquinone as an example, of the nucleophilic addition with formation of mono-,di-,tri, and tetra-susbtitution identification and quantification of quinones. An extensive literature search showed that among the methods, HPLC or HPLC/MS are the most often used methods.…”
Section: Analytical Methods For the Detection Of Quinonesmentioning
confidence: 99%
“…While best studied in insects, chemical defense is also well known from chelicerates (e.g., Eisner et al, 1961), with most of this work focused on opilionids (Roach et al, 1980;Raspotnig et al, 2010). Our experiments demonstrate, for the first time, that oil gland secretions of oribatid mites provide protection from predation by arthropod predators.…”
Section: Discussionmentioning
confidence: 70%